Application of the Principle of Al-Adah Muhakkamah in Mudharabah Practice - Arsiti, Nuri; Asmuni (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Customs that have taken root in society can be the basis for the formation of law. Such customs often arise because of human simplicity and because of their compatibility with human nature and needs in general. In the Islamic context, this view shows that Islam recognizes some good habits that have existed before in society by making modifications and renewals in accordance with better principles. This research aims to find out how the application of the Al-Adah Muhakkamah rule in mudharabah practices, as well as its impact on the fairness and efficiency of Islamic economic transactions. This research uses a literature study approach and content analysis to explore the application of the principle of Al-Adah Muhakkamah in mudharabah practice. Data were collected from various relevant literature sources, including journals, books, and relevant legal documents. The main findings show that the application of the Al-Adah Muhakkamah rule in mudharabah practice provides clarity and balance of rights and obligations between capital owners and business managers. Widely accepted customs in the community can fill in legal gaps that are not explicitly regulated in sharia texts, thereby improving the fairness and efficiency of transactions. The application of the Al-Adah Muhakkamah rule in mudharabah practice allows for fairer and more efficient transactions, and is in accordance with sharia principles. This shows that Islamic law can adapt to the times without disregarding the basic values of justice and benefit.